Preliminary Criteria and Stages of Selection of Young Students for Running in Sports Schools - Safarova Zebiniso Gulomali kizi (International Journal on Integrated Education, 2023)
One of the important tasks is to optimize the modern training system in the preparation of athletes and reserves who are members of the national teams of the Republic of Uzbekistan. At the same time, the strategy of developing innovative processes is considered one of the most important tasks at the moment.